Mechanism exploration and prognosis study of Astragali Radix-Spreading hedyotis herb for the treatment of lung adenocarcinoma based on bioinformatics approaches and molecular dynamics simulation - Guo, Junfeng; Zhao, Yuting; Wu, Xuanyu; Li, Ganggang; Zhang, Yuwei; Song, Yang; Du, Quanyu (Frontiers in Chemistry, 2023)
Background: Herb pair of Astragali Radix (AR) and Spreading Hedyotis Herb (SH) has been frequently prescribed in clinical for the treatment of lung cancer owing to its favorable efficacy. Yet, the mechanism under the therapeutic effects remained unveiled, which has limited its clinical applications, and new drug development for lung cancer. Methods: The bioactive ingredients of AR and SH were retrieved from the Traditional Chinese Medicine System Pharmacology Database, with the targets of obtained components predicted by Swiss Target Prediction. Genes related to lung adenocarcinoma (LUAD) were acquired from GeneCards, OMIM and CTD databases, with the hub genes of LUAD screened by CTD database. The intersected targets of LUAD and AR-SH were obtained by Venn, with David Database employed to perform Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses. Survival analysis of the hub genes of LUAD was carried out using TCGA-LUAD dataset. Molecular docking of core proteins and active ingredients was performed by Auto-Dock Vina software, followed by molecular dynamics simulations of protein-ligand complexes with well-docked conformations. Results: 29 active ingredients were screened out with 422 corresponding targets predicted. It is revealed that AR-SH can act on various targets such as EGFR, MAPK1, and KARS by ursolic acid (UA), Astragaloside IV(ASIV), and Isomucronulatol 7,2′-di-O-glucoside (IDOG) to alleviate the symptoms of LUAD. Biological processes involved are protein phosphorylation, negative regulation of apoptotic process, and pathways involved are endocrine resistance, EGFR tyrosine kinase inhibitor resistance, PI3K-Akt, and HIF-1 pathway. Molecular docking analysis indicated that the binding energy of most of the screened active ingredients to proteins encoded by core genes was less than −5.6 kcal/mol, with some active ingredients showing even lower binding energy to EGFR than Gefitinib. Three ligand-receptor complexes including EGFR-UA, MAPK1-ASIV, and KRAS-IDOG were found to bind relatively stable by molecular dynamics simulation, which was consistent with the results of molecule docking. Conclusion: We suggested that the herb pair of AR-SH can act on targets like EGFR, MAPK1 and KRAS by UA, ASIV and IDOG, to play a vital role in the treatment and the enhancement of prognosis of LUAD.